Development of Single-Phase Microbial Cementation Method and to Investigate its Efficacy on Bearing Capacity, UCS, and Permeability of Sandy Soils - Prakash Bhaskarrao Kulkarni; Pravin Dinkar Nemade; Ranjit Chavan; Manoj Pandurang Wagh (Journal of Engineering and Technological Sciences, 2021)
Microbially induced calcite precipitation (MICP) is a method based on collaborative knowledge of microbiology, chemistry and geotechnical engineering. The objective of this study was to investigate the increase of the bearing capacity and the unconfined compressive strength (UCS) as well as the reduction of the permeability of sandy soil using MICP. Experiments were carried out using Bacillus Pasteurii, on three different types of sand. The admixture of bacterial culture and cementation (BCC) solution all-in-one with sand by single-phase injection was applied to induce cementation. Three samples of the selected sand were treated with varied concentrations of BCC solution, ranging from 0.05 to 0.2 L/kg, with a curing period of 3, 7 and 14 days. The test results indicated an enhancement of 55% in UCS for sand treated with a BCC content of 0.05 to 0.2 L/Kg and a reduction of 40% in permeability for untreated sand with an effective diameter of 0.5 mm treated with 0.2 L/kg of BCC solution after 14 days of curing. The results of a plate load test (PLT) on MICP treated sand showed an increase in the ultimate bearing capacity (qu) by about 2.95 to 5.8 times and a 1.7 to 3.31-fold reduction in settlement corresponding to the same load applied on untreated footing. Further investigation of the size and shape of the bearing plate on bearing capacity and settlement was carried out through a plate load test. The higher and more favorable results shown by a rectangular plate compared to a circular plate indicate that the first is preferable.